The Impact of Income Tax on Economic Growth: Insights from Indonesia - Rhamadhani, Rika Febby (Yayasan Sinergi Kawula Muda, 2024)
This study examines the relationship between income tax policies and economic growth in Indonesia, focusing on their effects on investment, business expansion, and household consumption. While income tax is a fundamental instrument for fiscal revenue, excessive taxation may hinder private sector growth and reduce consumer spending, ultimately affecting overall economic stability. This research employs a mixed-methods approach, combining econometric modeling with qualitative interviews from key stakeholders, including government officials, economists, business owners, and financial consultants. Findings indicate that higher income tax rates can negatively impact investment and corporate expansion, particularly among SMEs. However, tax incentives and compliance enhancements contribute to improved economic activity. The study also highlights the role of digitalization in streamlining tax compliance and increasing government revenues without overburdening businesses. Furthermore, tax policy adjustments, including targeted incentives and simplified tax structures, are essential to balancing fiscal sustainability and economic growth. These findings emphasize the importance of tax policy reforms that foster a business-friendly environment while ensuring adequate government revenue. The study contributes to fiscal policy literature by providing empirical insights and policy recommendations. Future research should examine comparative tax policies in emerging economies and the long-term impact of tax reforms on economic resilience